Stabilitas Kimia Air Minum Dalam Kemasan Alkali Berdasarkan Langelier Saturation Index dan Endapan Kalsium Karbonat - Dandi Umar Faqih; Rusmini (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
Alkaline bottled drinking water is characterized by high pH and relatively high alkalinity, which may influence its chemical stability during storage. One commonly observed phenomenon is the formation of white precipitates that can reduce the perceived quality of the product. This study aimed to evaluate the chemical stability of alkaline bottled drinking water based on physicochemical parameter analysis, characterization of the formed precipitates, and calculation of the Langelier Saturation Index (LSI) as an initial indicator of calcium carbonate precipitation tendency. The study was conducted on ten alkaline bottled water samples from a single producer by measuring pH, temperature, total dissolved solids (TDS), alkalinity, and Ca²⁺ and Mg²⁺ ion concentrations. The white precipitates formed during storage were qualitatively analyzed and confirmed through reaction tests with hydrochloric acid. The results showed that all samples had pH values of 8.35-8.50, alkalinity of 146-154 mg/L as CaCO₃, and a dominance of Ca²⁺ ions over Mg²⁺ ions. All samples exhibited positive LSI values, indicating supersaturation with respect to calcium carbonate. These findings indicate that LSI is a relevant initial indicator for evaluating the chemical stability of alkaline bottled drinking water during storage.